Reduction of infectious intestinal diseases related to access to water and sewer services in Peru, 2002-2009 - Arenas-Significación, Fernando (2011)
Background: In Peru, intestinal infections rank third as cause of morbidity registered in outpatient settings. On the other hand access to water and sewage was respectively 74.7% and 62.8%. Objectives: To determine correlation of drinking water and sewage access and consultations for intestinal infectious diseases. Design: Ecological study of time series. Setting: Faculty of Medicine San Fernando, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material: Records from the Ministry of Health and Statistics and data from the Statistics and Informatics National Institute, Lima, Peru. Methods: A time series study was conducted based on records of the Ministry of Health on causes of morbidity in outpatients and data from the Statistics and Informatics National Institute records during the period 2002-2009. Results were analyzed using Spearman’s rho coefficient. Main outcome measures: Correlation coefficient. Results: An rho = -0.810, p = 0.015 was obtained for access to drinking water and infectious intestinal diseases relation, and an r = -0.714 p = 0.047 was obtained for access to sewage and infectious intestinal diseases relationship. Interpretation: It was found correlation between percentage of access to drinking water and drainage and percentage of outpatient visits for infectious intestinal diseases in the period 2002-2009 in Peru.